Characterization of Kodi Adu goats of Tamil Nadu, India - A.K. Thiruvenkadan; R. Saravanan; M. Chellapandian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A detailed study on distribution and performance of Kodi Adu breed of goats were made in the 253 herds of co-operating farmers in the 36 selected villages in its breeding tract. The study revealed that the Kodi Adu goats were mainly distributed in Thoothukudi and Ramanathapuram districts of southern Tamil Nadu and were tall, long, lean and leggy animals with compact body. Based on body colour, they were classified into two colour varieties viz. Chem-Porai and Karum-Porai. The least-squares means for height at withers, body length, chest girth, horn length, ear length, face length and tail length of fully grown adult goats (full mouth), were 84.94 ± 0.49, 77.56 ± 0.43, 79.28 ± 0.48, 16.16 ± 0.33, 15.91 ± 0.24, 17.79 ± 0.19 and 17.90 ± 0.25 cm respectively. The least-squares means for body weight at birth, three months, six months, nine months and 12 months of age were 2.81 ± 0.04, 11.41 ± 0.16, 14.70 ± 0.23, 16.79 ± 0.3 and 22.95 ± 0.31 kg respectively. The statistical analysis revealed a highly significant effect (P<0.01) of sex on body weight of Kodi Adu goats at different stages. The averages for age at first kidding and kidding intervals were 15.37 ± 0.08 and 7.67 ± 0.03 months respectively. Kodi Adu goats serve as the sole or subsidiary source of livelihood for a large number of small and marginal farmers and landless labourers in the breeding tract. The present population status explicitly does not warrant immediate conservation measures, however, initiation of Open Nucleus Breeding Scheme (ONBS) and forage and range development programmes should be made in its breeding tract for better productivity.